Vertical Clearance Analisis Pada Jembatan Jalan Tol Padang - Sicincin (Studi Area: Batang Tapakis) - Burnama, Nabila Siti (Jurnal Bangunan, Konstruksi & Desain, 2024)
The Padang-Sicincin Toll Road is one of the sections of the Padang-Pekanbaru Toll Road, which is one of the fins of the Trans Sumatra Toll Road. This Toll Road is a National strategic project from Presidential Regulation Number 58 of 2017. The Padang-Sicincin Toll Road section was built along 30.4 km and passes three rivers including Batang Anai, Batang Ulakan, and Batang Tapakis. This study chose the Batang Tapakis Bridge because there are several special conditions that are different from other bridges. The location of the Batang Tapakis Bridge was built near a river bend and adjacent to the Regency road so that the design of this bridge must consider the requirements of the Horizontal Clearance of the bridge. One of the bridge abutments is on the riverbank and the contractor plans to make a retaining wall and a buttock as a river embankment but causes the river cross-section to shrink. and can cause a rise in water level. As a result of this increase in water level, the bridge design must consider the requirements of the Vertical Clearance of the bridge. So this study analyzes the increase in water level before and after the bridge, and to find out whether the bridge design has met the Vertical and Horizontal Clearance standards. For hydrological calculations taken from PT.WIRATMAN data and this study will focus on river hydraulic calculations. River analysis using the HEC-RAS 5.0.5 application with a 100-year return period discharge of 179.4 m3/second. The results of the calculation are the difference in water level before and after the bridge is 1 m upstream of the bridge and 1.44 m downstream of the bridge. With this increase in water level, the Vertical Clearance of the bridge can be calculated, and it is found that the distance from the water level to the bridge is 3 m so that it does not meet the minimum requirement for Vertical Clearance of 5.1 m.